Ayurvedic Management of Infertility due to Anovulation- A Case Study - Sangeeta; Meena, Narendra Kumar; khathuria, Diksha (International Research Journal of Ayurveda & Yoga, 2023)
Background: Infertility is the failure to conceive even after one or more years of regular unprotected sexual intercourse. Due to improper life style ,incidence of infertility increases .PCOS is a life style disorder and very common among reproductive age group . Acharya Sushrut explained about Bandhya Yonivya pada where Nashtartava is mentioned as the one and only symptom. In Ayurveda text word Aartava has been used extensively in different contexts; menstrual blood, ovum and ovarian hormones. Therefore Amenorrhea, anovulation, hormonal dysfunction can be considered as visible manifestations of Nashtartva. Material and method: Following is a case report of a female who was anxious to conceive after 3 years of active married life, she had irregular menses. Her USG reports showed polycystic appearance of ovaries .The treatment adopted were to balance vata and kapha . Result: the treatment patient was a known case of infertility due to PCOS and after treatment her PCOS was cured and she conceived . Discussion: Line of treatment was to enhance potency of ovum for ovulation and regularize vitiated Vata Dosha, Shrotoshuddhi and Aartava janan. Conclusion: Ayurveda therapy can be used in patients of infertility due to PCOS for better outcome and no adverse drug effect was noticed.